Evaluation of PAUD (Early Childhood Education) Accreditation Program in Serang City (Research, Society and Development, 2020)
This research is aimed to increase the effectiveness of Early Childhood Education through evaluation of accreditation programs. By evaluating the PAUD accreditation program, it can be seen the overall phenomena of the evaluation which is principally for improvement in early childhood education, as well as to determine the success rate of the PAUD accreditation program in Serang City. This research approach is an Evaluation Research approach, the approach used descriptive approach. The qualitative approach creates a complex picture, examines the words, detailed reports and views of the respondents and conducts studies on natural situations. Evaluative research are the evaluative programs with using case studies method, this research are program evaluation with using CIPP (Context, Input, Process, Product) model which developed by Stufflebeam. The results shows that (1) evaluation on the context evaluation to good category, (2) the implementation of process evaluation are in the category enough (3)evaluation on the program preparation (input evaluation) part of most of them are at the Good category leveland (4) evaluation of the results and benefits of program activity implementation (Product Evaluation) is at the Good category level. Evaluation of PAUD Accreditation Program using the CIPP method, Based on the results of the previous evaluation, this study concluded that there are 14 (fourteen) aspects that have a "Good" value, namely aspects of facilities and infrastructure resources, human resource support, support for facilities and infrastructure, identification of scheduling programs, assessments, program outputs, and program outcomes of PAUD accreditation results are proposed, maintained and implemented.